Hyaluronic Acid-Based Dynamic Hydrogels for Cartilage Repair and Regeneration - Mingshuo Zhang; Qianwen Ye; Zebo Zhu; Shuanglian Shi; Chunming Xu; Renjian Xie; Yumei Li (Gels, 2024)
Hyaluronic acid (HA), an important natural polysaccharide and meanwhile, an essential component of extracellular matrix (ECM), has been widely used in tissue repair and regeneration due to its high biocompatibility, biodegradation, and bioactivity, and the versatile chemical groups for modification. Specially, HA-based dynamic hydrogels, compared with the conventional hydrogels, offer an adaptable network and biomimetic microenvironment to optimize tissue repair and the regeneration process with a striking resemblance to ECM. Herein, this review comprehensively summarizes the recent advances of HA-based dynamic hydrogels and focuses on their applications in articular cartilage repair. First, the fabrication methods and advantages of HA dynamic hydrogels are presented. Then, the applications of HA dynamic hydrogels in cartilage repair are illustrated from the perspective of cell-free and cell-encapsulated and/or bioactive molecules (drugs, factors, and ions). Finally, the current challenges and prospective directions are outlined.